Increasing rice yield with low ammonia volatilization by combined application of controlled-release blended fertilizer and densification - Xiaowei Ma; Zijuan Ding; Ren Hu; Xuexia Wang; Jun Hou; Guoyuan Zou; Bing Cao (PLoS ONE, 2025)
Controlled-release blended fertilizer (CRBF) and densification can increase rice yield and nitrogen (N) efficiency. However, the effects of CRBF combined with densification on rice yield, N absorption, economic benefits of fertilization, and ammonia volatilization loss remain unclear. A 2-year field experiment was conducted using five treatments: no N (control, CK), conventional N application (farmer’s fertilization practice, FFP), optimal N application (OPT), single basal application of CRBF (CRBF), and CRBF combined with densification (CRFDP). Moreover, rice yield, N absorption and use efficiency, economic benefit, and ammonia volatilization loss were evaluated. CRBF and CRFDP significantly increased rice dry matter, N use efficiency by 11.6%–30.5% and 90.2%–160.0%, finally increased the yield by 33.3% and 26.1% in 2021 and 2022, respectively. Compared with FFP, CRFDP with 16.7% reduction of N input significantly increased yield by 33.3% and 26.1% and economic benefit by 46.9% and 38.3% in 2021 and 2022, respectively. Compared with CRBF, CRFDP increased the total yield by 2.7% and 15.2%, economic benefit by 3.5% and 7.6%, and N absorption efficiency by 10% and 8.3% in 2021 and 2022, respectively. Compared with FFP, CRFDP reduced ammonia volatilization intensity by 62.5% and 60.8%, cumulative ammonia volatilization loss by 46.3% and 50.3% and also lowered NH4+-N of surface water by 69.0%–93.8% and 57.8%–89.7% in 2021 and 2022, respectively. The combination of CRBF and densification could improve the rice yield, economic benefit, and N use efficiency and reduce ammonia volatilization. These results might provide data and theoretical support for the high yield of rice and a new environmentally friendly and resource-efficient model of rice cultivation.